Status and legal effects of signature defects in the preparation of documents - Nader Pourarshad (مطالعات فقه و حقوق اسلامی)
Signing a writing is, in essence, a voluntary creation and one-sided legal act, the effectiveness of which, in addition to the ability of the signatory, requires two conditions, namely, the intention to act and the result. Formally, it should be the exclusive mark of hand rotation, fingerprint or stamp. If the signature is complete, it causes two legal and judicial effects in such a way that, firstly, it involves the apparent will in creating a creative legal act, the subject of the writing such as offer, acceptance, rescission or declarative such as confession, testimony and claim. Secondly, but what is a complete signature and what is the defect in the signature? What is its criterion and basis and what is its sanction? The present article answers each of these questions with a descriptive-analytical method and concludes that the signature in its general meaning may be single or multiple and is made in principle or representationally. In each case, the law, contract or effective declaration specifies that the signature is complete or incomplete. Incomplete signature is not effective, but as the case may be, it can be the cause and reason of civil, contractual and criminal responsibility for its owner.